South America Mi Hija: uma viagem épica pela América do Sul - Góis, Gisela Reis de (2020)
This doctoral dissertation aims to analyze the poem South America Mi Hija (1992), by the American Sharon Doubiago, from two main focuses: the epic characteristics of the work and the relevance of the presence of explanatory notes in the poem, which narrate a trip made by a mother and her daughter through South America, which marks the encounter of both with the historical and mythical past and the search for narratives of women who were lost in the course of History. The work presents a parallel with Persephone's vertical journey to the world of Hades and with the journey of Demeter, who moves horizontally, looking for her daughter. Regarding the explanatory notes, the approach discusses the two meanings of this presence. Using a qualitative method, first, the function of notes was analyzed, theoretically and critically, to promote the understanding of historical and mythical references - among others - of epics. Then, and more specifically in the case of the corpus under analysis, the approach discusses the creative conception of the poem and the very presence of referents linked to South America. The importance of analyzing the text and the paratext lies in the fact that the notes serve as keys for reading the poem, provided by the author herself. The main theoretical basis for this research is the theoretical and critical study of epic poems, such as those made by Anazildo Vasconcelos da Silva, Bernard Schweizer, Christina Ramalho and Fabio Mario da Silva, among others. These authors are essential for the composition of the first chapter, in which South America Mi Hija is analyzed according to the categories present in epic poetry. In the second chapter, I observe how the trip in South America Mi Hija allows the reader to know more about the South American peoples, since, through the characters who assume the role of travelers, the poem uses the drive of wandering to question which the real priorities of the current individual are, so ruled by capitalist consumerism and so absent from immaterial experiences. Also, in the second chapter, a discussion is presented on the relevance of the explanatory notes for the understanding of historical, mythological referents, etc. of epics. To support the approach and analysis of the notes present in South America Mi Hija, Paratexts, by Gérard Genette (2018), and The Tragic Origin of the German Footnote, by Anthony Grafton (1998) were used. The hypothesis that I advocate is that such referents are essential data for the epic reading and the reading of South America. Therefore, this study seeks to contribute to research on the production of epic poems by women and their popularization. I also hope to assist in the discussions on the footnotes in epics, measuring how such paratext can be relevant to the understanding of the creative concept and knowledge about different cultures, and, in the case of the work analized, about women and South America. For this reason, as one of the contributions of this research, planispheres about the journey in South America Mi Hija were made to better understand the narrative and geography of South America, also configuring the presence of a quantitative method. The thesis, first defended in the Doctoral Course of the Postgraduate Program in Letters at the University of Sergipe, aims to be configured as the inaugural critical fortune of this work by Doubiago in Brazil.